2003
DOI: 10.1021/jp022560l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cations in Infrared and Computational Analysis of Vanadium-Containing Six-Coordinate Oxotungstates

Abstract: Complex salts of VW 5 O 19 3-, cis-V 2 W 4 O 19 , 4-, and W 6 O 19 2-anions have been investigated using Fourier transform infrared spectroscopy and density functional theory computational methods. The intensities of the infrared absorption bands commonly used to identify the bridge and terminal oxygen atoms in these hexametalate systems were found to depend drastically on the nature of the countercation and presence of water in the salts. Theoretical investigations suggest that the anions alone may not show s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…Harmonic frequencies were obtained from analytical hessian calculations. As is well known the frequencies resulting from B3LYP DFT calculations are slightly too high, compared with experiments [22]. Commonly a scaling factor around 0.95 is used to correct for this deficiency [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Harmonic frequencies were obtained from analytical hessian calculations. As is well known the frequencies resulting from B3LYP DFT calculations are slightly too high, compared with experiments [22]. Commonly a scaling factor around 0.95 is used to correct for this deficiency [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…It has been successfully utilized before in our group to investigate the structural properties of Keggin structure polyoxometalates [16] and to investigate countercation and water bonding in Lindqvist structure polyoxometalates [17]. Although commonly used in this type of investigations and inexpensive, this basis set is rarely used in investigation of hydrocarbons or their fragments.…”
Section: Methodsmentioning
confidence: 99%
“…As we have reported previously for the 51 V NMR studies in Lindqvist and Keggin solids, both countercations and vanadium substitution modulates the electric field gradient of the vanadium center giving rise to substantial variations in the quadrupolar coupling parameters [40, 41]. The current and prior results make it clear that counter cations have to be explicitly included in computational models, which to the best of our knowledge has only been done in one study - our prior work on computing the vibrational frequencies in Lindqvist solids [16]. It will be interesting in the future to conduct these studies on Wells-Dawson series of compounds as well.…”
Section: Resultsmentioning
confidence: 99%
“…This understanding includes the knowledge of both the three-dimensional geometry of the extended solid (available from the single crystal X-ray diffraction in the cases where the solid can be crystallized) and the electronic structure of the anion and of vanadium center in particular. Advancements in theoretical quantum chemical methods have allowed for the investigations of Wells-Dawson (and generally polyoxometalate solids) [1620], and these studies are expected to aid in the interpretation of the experimental structural and spectroscopic data. We and others have shown that 51 V solid-state NMR spectroscopy can be used as a sensitive reporter of the structural and electronic environment of vanadium sites in a wide variety of inorganic and bioinorganic solids [2139] including polyoxometalates [4042].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation